Teman AI : Peran Character AI dalam Kehidupan Sosial Generasi Z - Sabrina Salsabila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Generation Z grew in the midst of rapid technological developments, including the use of Characters. Al, an artificial intelligence-based platform that allows interaction with virtual characters. This article explores the role of Character. Al supports self-expression, trains social skills, and overcomes loneliness in Generation Z. Findings show that this technology can provide significant benefits, especially in aspects of mental health and communication. However, challenges such as potential dependencies and data privacy issues are also a concern. By understanding the role and impact of Character. Al, Generation Z can use this technology wisely to support their social lives.